Sub-Acute Toxicity of Pigment Derived from Penicillium resticulosum in Mice - TATANG SOPANDI; WARDAH WARDAH (Microbiology Indonesia, 2012)
Pigments derived from Penicillium have different toxicities depending on the pigment components. This study was intended to evaluate the sub-acute toxicity of oral exposure of Balb/c mice to Penicillium resticulosum pigment. A total of 50 healthy adult male and female mice were divided into 5 treatment groups and different doses of pigment (0, 125, 250, 500, and 1000 mg kg-1 weight) were orally administered. Oral feeding of pigment with doses 125 to 1000 mg kg-1 body weight daily to adult mice did not cause mortality nor any clinical abnormalities. There were no significant differences in body, liver and kidney weights, nor liver and kidney functions of mice when pigment was given orally with intake doses of 125 to 1000 mg/kg body weight daily for 28 d in comparison to mice without pigment intake (control groups). There is a slight difference in liver histopathology of mice exposed to 500and 1000 mg/kg body weight of pigment for 28 d in comparison to mice control groups, although there were no differences in kidney histopathology. Thus, we can conclude that the pigment of P. resticulosum can be cathegorized as low toxic pigment and well tolerated at dose below 500 mg kg-1 body weight daily for 28 d.